Uji Aktivitas Ekstrak Etanol Okra Hijau (Abelmoschus esculentus L.) sebagai Penumbuh Rambut Pada Kelinci Jantan - Naimatul Retno Faizah; Tresa tyas Margaretha (JURNAL FARMASI DAN MAKANAN, 2024)
Reduced hair density is a hallmark of hair loss, a medical condition. A deficiency in hair nourishment is one of the reasons of hair loss. The compounds in green okra include tannins, alkaloids, and flavonoids, are ingredients that may promote hair development. The purpose of this study was to study the effect of green okra ethanol extract on the hair development of male white rabbits and identify the optimal dose for this purpose is the main objective of this research. This study used a true experimental method. The hair-fertilizing activity test of green okra ethanol extract was carried out on 6 rabbits as positive control, negative control, normal control and samples with extract doses of 5%,10%, 20%. The results of the study showed that the average hair growth of rabbits with concentrations of 5%, 10% and 20% was 12.12 mm, 13.62 mm and 16.06 mm. The results of the anova test were 0.000. The conclusion of this study is that there is an effect of green okra ethanol extract on rabbit hair growth.